A study on the coefficient of discharge through the suction or discharge ports of RV expander - Seow, Ee Hung. (2010)
The carbon dioxide (CO2) refrigeration system has seen increasing interest in recent years. Since the ban on conventional ozone-depleting refrigerants, many have proposed CO2 as an alternative refrigerant. But high throttling losses involved in CO2 refrigeration cycle leads to low efficiency of the system. It is suggested that by replacing the conventional expansion valve with an expander, the efficiency of such a system can be greatly improved.